2019
DOI: 10.4046/trd.2018.0045
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Phenotype of a First Unprovoked Acute Pulmonary Embolism Associated with Antiphospholipid Antibody Syndrome

Abstract: BackgroundAntiphospholipid antibody syndrome (APS), an important cause of acquired thrombophilia, is diagnosed when vascular thrombosis or pregnancy morbidity occurs with persistently positive antiphospholipid antibodies (aPL). APS is a risk factor for unprovoked recurrence of pulmonary embolism (PE). Performing laboratory testing for aPL after a first unprovoked acute PE is controversial. We investigated if a specific phenotype existed in patients with unprovoked with acute PE, suggesting the need to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(42 reference statements)
2
3
0
2
Order By: Relevance
“…In this study, there were more low-risk patients observed in the APS-PE group, especially in triple positive aPLs patients. This was consistent with previous studies, which found 62.5% of low-risk patients in the APS-PE group and only 29.5% in the non-APS-PE group ( 19 ). Therefore, the aPLs test should not be ignored for patients with low-risk pulmonary embolism.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, there were more low-risk patients observed in the APS-PE group, especially in triple positive aPLs patients. This was consistent with previous studies, which found 62.5% of low-risk patients in the APS-PE group and only 29.5% in the non-APS-PE group ( 19 ). Therefore, the aPLs test should not be ignored for patients with low-risk pulmonary embolism.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies ( 19 ), prolonged APTT was an indicator of APS in young PE patients. The LA antibody may inhibit the formation of prothrombinase complexes, leading to prolonged APTT ( 32 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Third, the time in therapeutic range of the international normalized ratio was not available for assessing the degree of quality control in the study. Fourth, antiphospholipid syndrome is an important risk factor for an increased risk for the first and recurrent VTE343536. However, in this study, the test for antiphospholipid antibody was rarely performed and excluded from the variables for risk factors.…”
Section: Discussionmentioning
confidence: 89%